The impact of waste management practices on youth development in Mombasa, Kenya: A human resource and environmental sustainability perspective - Nyongesa, Wesonga Justus; Westhuizen, Johan Van Der (International Journal of Innovative Research and Scientific Studies, 2025)
This study set out to explore how waste disposal practices impact youth development in Mombasa, Kenya, with a specific focus on human resource involvement and environmental sustainability. Given that solid waste management is a global challenge with local consequences, the research aimed to understand the extent to which youth participation in waste management contributes to their personal and social development. A survey research design was adopted, utilizing purposive sampling to select respondents. Out of 300 targeted youth waste collectors in urban Mombasa, a sample of 175 was drawn using the Taro Yamane formula, ensuring statistical confidence. Data was gathered through triangulated methods, primarily structured questionnaires. To ensure reliability, a pilot study was conducted in Nakuru City. The data collected was analyzed using SPSS, generating descriptive statistics and inferential analyses such as t-tests, ANOVA, and correlation analysis. Findings were presented through visuals including figures and tables. The analysis revealed a statistically significant positive correlation between youth participation in waste disposal and their development (r = 0.439, p = 0.000). Regression analysis confirmed that young people play a pivotal role in addressing urban sustainability challenges. The majority of respondents recognized and affirmed the value of youth engagement in waste management programs, linking their involvement to improved life skills, environmental awareness, and community leadership. The study concludes that youth participation in solid waste management has a meaningful and measurable impact on their development. By rejecting the null hypothesis, the research confirms that such involvement is not only beneficial for environmental outcomes but also critical in shaping proactive, empowered, and skilled youth in urban Kenya. These findings underscore the importance of integrating youth into formal waste management strategies. Policymakers, development partners, and local authorities should consider structured programs that empower young people as environmental stewards. Future research should explore longitudinal impacts, adopt qualitative approaches, and consider policy frameworks and innovative technologies to enhance waste management effectiveness. Ultimately, empowering youth in this space supports both environmental goals and sustainable youth development.